COMPARISON OF THE IMPACT OF THE IMPLEMENTATION OF THE CAPITALIST ECONOMIC SYSTEM ON COMMUNITY WELFARE BY THE UNITED STATES AND CHINA - Rimapradesi, Yulia; Putri, Mia Utami; Noveri, Aurelia Putri (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2023)
Capitalist economics is an ideology introduced by Adam Smith as an economic system controlled by the private sector and the government does not play too much of a role in trading activities. However, if we look at the bad impact of the Capitalist economic system, there is a social gap between rich and poor people. Because in this system the private sector has the right to seek maximum profits in any way and has the right to increase its business. while ordinary workers can only work and receive wages from the rich, so that the rich get richer and the poor get poorer. So this research will discuss the impact of the implementation of the capitalist economic system on the welfare of society in the United States and China, and whether the progress of these two countries can improve the prosperity of their society. This research uses a qualitative method based on existing literature and information discussing the case. The results of this research are that the United States and China as developed countries and dominate international markets cannot avoid cases of social inequality among their communities. The intensity of the phenomenon of inequality of opinion and even gender continues to narrow, facilities such as education and health in cities and villages are very different, many children in villages experience delays in receiving education compared to children who live in urban areas.